PENANAMAN KARAKTER SOPAN SANTUN OLEH GURU PKN DI SMA NEGERI 1 SUKADANA KABUPATEN KAYONG UTARA - Rahmadi, Debi (JURNAL PENDIDIKAN KEWARGANEGARAAN, 2017)
The study aimed to obtain information on: (1) The Character Form of Grace Students Class XI SMA Negeri 1 Sukadana Kayong Utara; (2) The Civic Guru's Efforts in Initiating the Character of the Graceful of the Grade XI Students of SMA Negeri 1 Sukadana of Kayong Utara Regency; (3) Factor inhibiting the Cultivation of Polite Character of Class XI of SMA Negeri 1 Sukadana of Kayong Utara Regency. The research method used is qualitative method with qualitative descriptive research. Data analysis is done by reduction data, collecting data, display data and verification data. the subject of research in this study is the teacher of Civics, while the object of this study students class XI SMA Negeri 1 Sukadana Kayong Utara. Data collection techniques such as observation techniques, direct communication techniques and documentary study techniques. The data collection tools used are observation guides, interview guides and documents.